G. J. Billberg’s (1833) ‘On the ichthyology, and description of some new fish species of the pipefish genus Syngnathus’ - Kullander, Sven O. (Zootaxa, 2016)
Gustaf Johan Billberg’s review of ichthyology, published in Swedish in 1833 in the Linnéska samfundets handlingar, mentions 92 fish taxa at genus and species level, 41 of which represent new taxa, unnecessary replacement names, or unjustified emendations. Billberg presents his own classification of fishes, in which five new family names are introduced: Ballistidae, Diodontidae, Ooididae, Chironectidae, and Macrorhyncidae. Diodontidae has priority over Diodontidae Bonaparte, 1835. Macrorhyncidae was published earlier than Gempylidae Gill, 1862, but the latter has priority by prevailing usage.        Billberg mentions 61 genera of fishes, 41 of them listed only by name. Six generic names proposed by Billberg are available as unjustified emendations: Myxinus, Petromyzus, Scylia, Mustellus, Zyganna, and Ballistes. Brachionus is an unnecessary replacement name. Aphrus, Capriscus, Exormizus, Enneophthalmus, and Oedaus are nomina nuda. Eight new genera of fishes are proposed: Anodon, Posthias, Orbis, Sphaeroides, and Ooides are junior synonyms; Cotilla is a nomen oblitum in relation to Sufflamen Jordan, 1916; Tropigaster a nomen oblitum in relation to Aracana Gray, 1835; and Tetragonizus a nomen oblitum in relation to Lactoria Jordan & Fowler, 1902.        Billberg lists 31 species of fishes. Three represent new combinations; two are nomina nuda. The following 14 new species are described based on literature: Raja forskohlii, Cephaloptera dumerillii, Myliobatis lacepedei, Scylia russelii, Anodon macropterus, Cotilla frenata, Monacanthus blochii, M. sebae, M. cuvieri, M. marcgravii, Tetraodon striatus, Orbis psittacinus, Orbis punctulatus, and Orbis guttatus. All of those are invalid, except Scylia russelii, which is a species inquirenda. The following nine species group names are unnecessary replacement names and consequently invalid: Raja arabica, Myliobatis rissoi, Scylia isabellina, Anodon cirrhosus, Anodon cornutus, Zyganna voracissima, Centrina broussonetii, Acipenser vulgaris, and Acipenser ichthyocolla.        Three species of pipefishes of the family Syngnathidae are described and figured by Billberg from drawings of specimens observed on the Swedish West Coast. Syngnathus virens and S. pustulatus are junior synonyms of S. typhle Linnaeus, 1758. Syngnathus palmstruchii is a junior synonym of Entelurus aequoreus (Linnaeus, 1758).